2021
DOI: 10.20944/preprints202102.0231.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Etiology of Acute Leukemia. A Review

Abstract: Acute leukemias constitute some of the most common malignant disorders. Despite significant progress made in the treatment of these disorders, their etiology remains unknown. A large and diverse group of genetic and environmental variables have been proposed. The role of a variety of factors, including pre-existing and acquired genetic mutations, exposure to radiation and various chemicals during pre-conception, pregnancy and throughout life have been explored. The effects of inherited genetic variations and d… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 149 publications
(197 reference statements)
0
5
0
Order By: Relevance
“…Geographically, the distribution of leukemia burden is patterned by country-level development, with age-standardized incidence, and mortality higher in more developed countries. In this study, some risk factors are not included due to data missed however, many factors may be important to evaluate leukemia occurrence such as exposure chemicals to radiation, chemotherapy, genetic syndromes, and lifestyle factors like smoking [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Geographically, the distribution of leukemia burden is patterned by country-level development, with age-standardized incidence, and mortality higher in more developed countries. In this study, some risk factors are not included due to data missed however, many factors may be important to evaluate leukemia occurrence such as exposure chemicals to radiation, chemotherapy, genetic syndromes, and lifestyle factors like smoking [7].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it was found that countries with higher income levels had a higher incidence of 1.5 times higher than low-income countries [6]. GLOBOCAN 2020 estimated that leukemia was the 15th most frequently diagnosed cancer worldwide and it is ranked as the 11th leading cause of cancer-related mortality, accounting for about 4.7% of all cancer-related deaths [4,7]. Pathophysiological, leukemia occurs due to the malignant transformation of pluripotent hematopoietic stem cells (both myeloid and lymphoid precursors).…”
Section: Introductionmentioning
confidence: 99%
“…Some of the known DNA viruses that are capable of causing human cancers are Epstein-Barr (EB) virus, human papilloma virus, hepatitis B virus, and human herpes virus 8. The relationship of EB virus to the development of Burkitt's lymphoma and nasopharyngeal carcinoma is well established [53][54][55][56][57][58][59]. Likewise, the relation of human papilloma virus and the development of cervical cancer and retention of HPV viral oncoproteins E6 and E7 for their continued expression and proliferation has been demonstrated [60][61][62][63].…”
Section: Viruses and Human Cancermentioning
confidence: 99%
“…1 Recent revolution in next-generation sequencing has uncovered many novel somatic mutations and rearrangements in ALL cells, which have prognostic and therapeutic implications. 2,3 Similarly, it has led to recognition of germline variants in the same genes (e.g., PAX5, ETV6, and IKZF1) with somatic mutations commonly associated with ALL (►Table 1). 4,5 Apart from increasing the risk of developing ALL, germline variants may influence diagnostic testing, genetic counseling, and response to antileukemic treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Down's syndrome, Shwachman's syndrome, Fanconi anemia, Bloom's syndrome, neurofibromatosis, and ataxia telangiectasia are well-recognized conditions associated with ALL. 3 In this report, we describe novel association of T-cell ALL (T-ALL) with tuberous sclerosis (TS), also known as tuberous sclerosis complex (TSC). TSC is autosomal dominant neurocutaneous syndrome characterized by formation of benign hamartoma in various tissues including brain, heart, and kidneys.…”
Section: Introductionmentioning
confidence: 99%